Estrategia comunicacional para la promoción de la equidad de género y cumplimiento de los derechos humanos en el colegio particular Juan Montalvo sección bachillerato - Pijuana Erique, Tatiana Alejandra (2015)
Since in the Ecuador human rights and gender equality are taking great importance in comparison with past years, the issue raised in this thesis taking as a study group for adolescents of private school Juan Montalvo city of Loja originated . The main objective of this work has been the development of a communications strategy to promote human rights and gender equity in that institution, especially aimed at students of the high school section. Starting from a survey of high school students of this educational institution, two aspects are determined, the first students to mention the lack of teachers trained in issues related to rights and equity, and the second by the lack of promotion topics mentioned students know the importance of keeping force in their educational establishment. It is worth mentioning that this thesis was conducted on a population of 150 students of that institution, distributed over the three years of high school, the result of the study conducted locate three relevant points; The first is that the subject human rights and gender equality is not raised in the curriculum of the establishment, the second is the need to show the students to have a mediator as an educational psychologist for the different existing issues in their establishment and finally the need to use digital media as a tool for promotion and communication of these issues.